ANALISIS MISKONSEPSI PADA MATERI KPK DAN FPB DI KELAS IV SEKOLAH DASAR - Yuliani, Neni; Hepsi Nindiasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics needs to be taught to students from elementary school so that students have the ability to think logically, analytically, systematically, critically, creatively and collaboratively. Because mathematics is in everyday life, a teacher must be able to instill mathematical concepts and be able to provide mathematical understanding to his students. However, the mismatch between students' initial understanding and actual concepts can affect the formal learning process. This has an impact on the understanding of the knowledge conveyed by teachers and is often difficult to change. This condition causes students to believe that a false concept is true, which is known as a misconception. This research uses a qualitative descriptive approach. Data collection techniques were carried out through tests to identify student misconceptions and interviews. The instruments used in this research include test sheets designed to reveal students' misconceptions about the KPK and FPB material. interviews for students who experience misconceptions with the aim of finding out the factors causing misconceptions. In the KPK and FPB material in class IV, there are several misconceptions among students who are taught through multiples, LCM, and factor trees. In determining the KPK and FPB, they are taught in another way, namely by plotting rice fields.